Bentuk Dan Fungsi Balai Basarah Hindu Kaharingan Di Desa Pangi Kecamatan Banama Tingang Kabupaten Pulang Pisau - Made Paramarta (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2022)
A holy place is a place that must be owned by every religious community. Hindu holy place is a place which is very sacred and sacred for Hindus. Faceted sacred place of Hindus in Indonesia built in accordance with desa, kala and patra. There is a tangible temple, temple, statues, and balai Basarah. Balai Basarah is a kind of holy place of Hindu Kaharingan located in Central Kalimantan. Balai Basarah have a different shape in every district in Central Kalimantan are shaped, house, and meru. Balai Basarah have other functions, in addition to the main functions, namely as a place of worship. Another function, namely as a place of education, the implementation of a religious ritual, and celebration of holy days of religious. See the forms and functions of the balai Basarah, researchers are interested to study the characteristic form of balai Basarah because it has reliefs and artistic regionalism that need to be preserved. The functions of the balai Basarah have some function other than as a place of worship, it is very interesting to be dissected in depth so as to present a piece of writing that is interesting about the form and functions of the balai Basarah Hindu Kaharingan.